2008
DOI: 10.1111/j.1439-0396.2007.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different liquid cultures of live yeast strains on performance, ruminal fermentation and microbial protein synthesis in lambs

Abstract: Three yeast strains, Kluyveromyces marximanus NRRL-3234 (KM), Saccharomyces cerevisiae NCDC-42 (SC) and Saccharomyces uvarum ATCC-9080 (SU), and a mixed culture (1:1:1 ratio) were evaluated for their value as probiotics in lamb feeding in two experiment. In experiment I and II, 20 and 30 pre-weaner lambs were fed for 63 and 60 days in two and three equal groups respectively. All lambs were offered ad libitum a creep mixture and Zizyphus nummularia leaves, and yeasts were dosed orally. In experiment I, one grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
8
27
0
1
Order By: Relevance
“…Marden et al (6) observed increased total tract digestibility of NDF and ADF when dairy cows were fed a diet with live yeast. In contrast to the cited authors, Tripathi et al (7) showed that neither NDF nor ADF were influenced when the diet was supplemented with live S. cerevisiae. The yeast additive can reduce lactate accumulation in the rumen (6) by increasing the count of lactate-utilizing bacteria, particularly Selenomonas ruminantium, and also by decreasing the number of the lactate-producing bacteria, Streptococcus bovis (3).…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Marden et al (6) observed increased total tract digestibility of NDF and ADF when dairy cows were fed a diet with live yeast. In contrast to the cited authors, Tripathi et al (7) showed that neither NDF nor ADF were influenced when the diet was supplemented with live S. cerevisiae. The yeast additive can reduce lactate accumulation in the rumen (6) by increasing the count of lactate-utilizing bacteria, particularly Selenomonas ruminantium, and also by decreasing the number of the lactate-producing bacteria, Streptococcus bovis (3).…”
Section: Introductionmentioning
confidence: 51%
“…In the current study, the total tract digestibility of other nutrients did not increase when yeast was added to the diet. Most literature data show no improvement in digestibility of dry matter and organic matter when live yeast is added to the ration (7,16,17). In several trials, higher dry and organic matter digestibility was reported (6,18) when live S. cerevisiae cells were supplemented, due to the increased structural carbohydrate digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Several microbial species, mainly bacteria (lactic acid and non-lactic acid bacteria), yeasts (dairy strains) or fungi are considered as probiotics (Tripathi et al 2008).…”
Section: Definitions and Types Of Probioticsmentioning
confidence: 99%
“…Some researchers have found no effect in rumen pH of small ruminants (Doreau et al 1998, Tripathi et al 2008), whilst others have recorded an increase in rumen pH (Radev 1999, Abd El-Ghani 2004. In contrast, Kowalik et al (2011) and Tripathi and Karim (2011) have reported a reduction in rumen pH after supplementation with Saccharomyces uvarum (ATCC9080; SU) or an equal mixture of Kluyveromyces marximanus (NRRL3234; KM), Saccharomyces cerevisiae (NCDC42; SC) and S. uvarum (ATCC9080; SU) to growing lambs.…”
Section: Rumen Phmentioning
confidence: 99%
“…Increased live weight gain and feed conversion upon supplementation with Celmanax ® was associated to improved efficiency of fermentation (stimulation of microbial growth, activity and increased proportion of available carbon towards microbial protein synthesis), that might have diverted balanced supply of nutrient towards cell growth Tripathi and Karim, 2011). Others have observed increased live weight gain and feed conversion due to supplementation with yeast (Abdelrahman and Hunaiti, 2008;Lesmeister et al, 2004;Tripathi and Karim, 2011), while others have not (Titi et al, 2008;Tripathi et al, 2008). This study demonstrated that Celmanax® supplementation have the potential of improving intake, live weight gain and feed conversion efficiency, hence its application as possible feed additives in small ruminants.…”
Section: Discussionmentioning
confidence: 99%